STRUCTURAL GEOLOGY AND MAGMATISM/VOLCANISM ACTIVITY TOWARD GEOMORPHOLOGY IN BANDUNG BARAT-CIRANJANG, WEST JAVA - Haryanto, Iyan; Ilmi, Nisa Nurul; Hutabarat, Johanes; Natasia, Nanda; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2019)
Geomorphology along Ciranjang to Bandung Barat is dominated by structural hills while others are related to the magmatism/ volcanism activity. The others morphological features are plain land which belong to Ciranjang and Bandung depression. In interpreting geological structures, topography map and DEM were used together with field data particularly the landscape faulting indication and flow pattern. The compiled data of morphology, stratigraphy and landscape in the study area showed that the geomorphology of the area could be differ into several unit which are structural hill, non-structural hill, and plain morphology units. Sedimentary structural hill unit were develop in Rajamandala hills starting from the Cianjur-Bandung border, Solitary hills geomorphological unit developed in Cililin area, and the developed plain unit developed in Ciranjang and Cililin area